A comparative study of intrathecal nonopioid adjuvants to hyperbaric bupivacaine for spinal anaesthesia - Joshi, Suchita A.; Khadke, Venkatesh V. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Intrathecal drugs when used as adjuvant to spinal anaesthesia produce substantial anti-nociception and potentiate analgesia of bupivacaine. This study was planned to evaluate the effects of intrathecal non opioid drugs-clonidine, midazolam, neostigmine and magnesium sulphate on duration of analgesia, characteristics of SA and hemodynamic stability when added to 0.5% hyperbaric bupivacaine for spinal anaesthesia. Methods: In this randomized, prospective, double blind study, 100 ASA physical status I and II adults patients posted for elective lower abdominal surgery were divided into 4 groups (n=25). Group BN received preservative free neostigmine 25µg, group BMG received Mgso4 50mg, group BC received clonidine 30µg and BM received midazolam 2mg with 15mg hyperbaric bupivacaine. Duration of postoperative analgesia, effect on onset and duration of sensory and motor block, incidence of side effects was noted. Continuous variables were compared using one way Analysis of Variance (ANOVA). Results: The duration of postoperative analgesia was significantly prolonged in BM group 391.64 (132.98) minutes, followed by BN group 308.76 (127.40), BC group 296.60 (52.77) and BMG group 252.2 (86.76). The numbers of analgesic doses in 24 hours were significantly less in BM group. One patient required additional analgesia in BM group as against 40%, 36% and 64% in BN, BC, BMG group respectively. The duration of sensory block was significantly prolonged in group BM followed by group BC and BN. Conclusions: Intrathecal midazolam provides superior analgesia without clinically relevant side effects. The onset of analgesia was rapid and duration prolonged with intrathecal midazolam followed by neostigmine and clonidine.